Are Apathy and Depressive Symptoms Related to Vascular White Matter Hyperintensities in Severe Late Life Depression?. (January 2021) - Oudega, Mardien Leoniek; Siddiqui, Amna; Wattjes, Mike P.; Barkhof, Frederik; Kate, Mara ten; Muller, Majon; Bouckaert, Filip; Vandenbulcke, Mathieu; De Winter, François-Laurent; Sienaert, Pascal; Stek, Max L.; Comijs, Hannie C.; et al.
Objective: Apathy symptoms are defined as a lack of interest and motivation. Patients with late-life depression (LLD) also suffer from lack of interest and motivation and previous studies have linked apathy to vascular white matter hyperintensities (WMH) of the brain in depressed and nondepressed patients. The aim of this study was to investigate the relationship between apathy symptoms, depressive symptoms, and WMH in LLD. We hypothesize that late-onset depression (LOD; first episode of depression after 55 years of age) is associated with WMH and apathy symptoms. Methods: Apathy scores were collected for 87 inpatients diagnosed with LLD. Eighty patients underwent brain magnetic resonance imaging. Associations between depressive and apathy symptoms and WMH were analyzed using linear regression. Results: All 3 subdomains of the 10-item Montgomery–Åsberg Depression Rating Scale correlated significantly with the apathy scale score (all P < .05). In the total sample, apathy nor depressive symptoms were related to specific WMH. In LOD only, periventricular WMH were associated with depression severity (β = 5.21, P = .04), while WMH in the left infratentorial region were associated with apathy symptoms (β coefficient = 5.89, P = .03). Conclusion: Apathy and depressive symptoms are highly overlapping in the current cohort of older patients with severe LLD, leading to the hypothesis that apathy symptoms are part of depressive symptoms in the symptom profile of older patients with severe LLD. Neither apathy nor depressive symptoms were related to WMH, suggesting that radiological markers of cerebrovascular disease, such as WMH, may not be useful in predicting these symptoms in severe LLD.